Muse Cells: Nontumorigenic Pluripotent Stem Cells Present in Adult Tissues-A Paradigm Shift in Tissue Regeneration and Evolution - Ariel A. Simerman; Julia D. Phan; Daniel A. Dumesic; Gregorio D. Chazenbalk (Hindawi Limited, 2016)
Muse cells are a novel population of nontumorigenic pluripotent stem cells, highly resistant to cellular stress. These cells are present in every connective tissue and intrinsically express pluripotent stem markers such as Nanog, Oct3/4, Sox2, and TRA1-60. Muse cells are able to differentiate into cells from all three embryonic germ layers both spontaneously and under media-specific induction. Unlike ESCs and iPSCs, Muse cells exhibit low telomerase activity and asymmetric division and do not undergo tumorigenesis or teratoma formation when transplanted into a host organism. Muse cells have a high capacity for homing into damaged tissue and spontaneous differentiation into cells of compatible tissue, leading to tissue repair and functional restoration. The ability of Muse cells to restore tissue function may demonstrate the role of Muse cells in a highly conserved cellular mechanism related to cell survival and regeneration, in response to cellular stress and acute injury. From an evolutionary standpoint, genes pertaining to the regenerative capacity of an organism have been lost in higher mammals from more primitive species. Therefore, Muse cells may offer insight into the molecular and evolutionary bases of autonomous tissue regeneration and elucidate the molecular and cellular mechanisms that prevent mammals from regenerating limbs and organs, as planarians, newts, zebrafish, and salamanders do.